2018
DOI: 10.5152/tpd.2018.5137
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Evaluation of Patients Diagnosed with Cystic Echinococcosis at Kafkas University Faculty of Medicine’s Surgical Outpatients Unit

Abstract: We concluded that CE is an important public health problem for the Kars region due to a low socioeconomic and educational level, where livestock breeding is also common. More comprehensive epidemiological studies should be undertaken and national control programs are required to keep the disease under control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Women represent the majority of adult cases (Botezatu et al 2018, Tamarozzi et al 2018, Aydin and Adigu ¨zel 2019. In this context, Aydın and Adigu ¨zel (2019) found that 65.6% of their 482 patients were women, whereas Mor et al (2018) have reported a figure of 79.1%. However, a predominance of male cases has also been documented in some studies (Shams-Ul- Bari et al 2011, Tartar et al 2020.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Women represent the majority of adult cases (Botezatu et al 2018, Tamarozzi et al 2018, Aydin and Adigu ¨zel 2019. In this context, Aydın and Adigu ¨zel (2019) found that 65.6% of their 482 patients were women, whereas Mor et al (2018) have reported a figure of 79.1%. However, a predominance of male cases has also been documented in some studies (Shams-Ul- Bari et al 2011, Tartar et al 2020.…”
Section: Discussionmentioning
confidence: 97%
“…Monitoring women and over 30-year-old age group are very crucial in terms of preventing alveolar echinococcosis (Wang et al 2020). In this As elsewhere in the world, hepatic and pulmonary echinococcosis are most commonly seen in Turkey (Botezatu et al 2018, Mor et al 2018, Tartar et al 2020. A single lesion in a single organ occurs in the majority of the cases (40-80%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of urinary parasites, the incidence is clinically rare compared to GI tract parasites [10][11][12]55,56]. The rarity perhaps due to mild or transient or even non-specific symptom which sometime make it unnoticed/neglected [57] even overlooked [58] by clinician or lab tech.…”
Section: Parasitology Urinalysismentioning
confidence: 99%